Changes in verbal and visuospatial working memory from Grade 1 to Grade 3 of primary school: Population longitudinal study. (11th December 2017) - Nicolaou, E.; Quach, J.; Lum, J.; Roberts, G.; Spencer‐Smith, M.; Gathercole, S.; Anderson, P. J.; Mensah, F. K.; Wake, M.
Abstract: Background: Adaptive working memory training is being implemented without an adequate understanding of developmental trajectories of working memory. We aimed to quantify from Grade 1 to Grade 3 of primary school (1) changes in verbal and visuospatial working memory and (2) whether low verbal and visuospatial working memory in Grade 1 predicts low working memory in Grade 3. Method: The study design includes a population‐based longitudinal study of 1, 802 children (66% uptake from all 2, 747 Grade 1 students) at 44 randomly selected primary schools in Melbourne, Australia. Backwards Digit Recall (verbal working memory) and Mister X (visuospatial working memory) screening measures from the Automated Working Memory Assessment ( M = 100; SD = 15) were used to assess Grades 1 and 3 (ages 6–7 and 8–9 years) students. Low working memory was defined as ≥1 standard deviation below the standard score mean. Descriptive statistics addressed Aim 1, and predictive parameters addressed Aim 2. Results: One thousand seventy (59%) of 1802 Grade 1 participants were reassessed in Grade 3. As expected for typically developing children, group mean standard scores were similar in Grades 1 and 3 for verbal, visuospatial, and overall working memory, but group mean raw scores increased markedly. Compared to "not low" children, those classified as having low working memory in Grade 1 showed much larger increases in both standard and raw scores across verbal, visuospatial, and overall working memory. Sensitivity was very low for Grade 1 low working memory predicting Grade 3 low classifications. Conclusion: Although mean changes in working memory standard scores between Grades 1 and 3 were minimal, we found that individual development varied widely, with marked natural resolution by Grade 3 in children who initially had low working memory. This may render brain‐training interventions ineffective in the early school year ages, particularly if (as population‐based programmes usually mandate) selection occurs within a screening paradigm.